2023
DOI: 10.1093/noajnl/vdad059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recurrence probability following radiotherapy in patients with CNS WHO grade 2 meningioma using integrated molecular-morphologic classification

Abstract: Background The current CNS WHO classification of brain tumors distinguishes three malignancy grades in meningiomas, with increasing risk of recurrence from CNS WHO grade 1 to 3. Radiotherapy is recommended by current EANO guidelines for patients not safely amenable to surgery or after incomplete resection in higher grades. Despite adequately predicting recurrence probability for the majority of CNS WHO grade 2 meningioma patients, a considerable subset of patients demonstrates an unexpectedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Only by doing so, one can adequately assess the efficacy and safety of an experimental treatment. Therefore, retrospective molecular work-up should be considered to determine the actual biological aggressiveness of the included tumors as suggested by others [ 26 ]. Thus, future meningioma trials should consider the use of molecular characteristics to stratify patients in the first place to improve comparability and cohort homogeneity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only by doing so, one can adequately assess the efficacy and safety of an experimental treatment. Therefore, retrospective molecular work-up should be considered to determine the actual biological aggressiveness of the included tumors as suggested by others [ 26 ]. Thus, future meningioma trials should consider the use of molecular characteristics to stratify patients in the first place to improve comparability and cohort homogeneity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a classification integrating microscopic features, copy number variation, and methylome classification, Deng et al stratified 44 patients with G2 meningiomas into 3 risk groups (low, intermediate, and high-risk). 29 Such risk stratification better-reflected differences in 3-year local progression-free survival (lPFS) following RT. In fact, the 3-year lPFS rates reported in this study ranged from 100% for the low-risk group to 75.5% for the high-risk group.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the 9 studies reviewed specifically report the incidence and severity of acute and late toxicities (AT and LT). 16 , 23 , 28 , 29 , 24 The incidence of G ≥ 3 adverse events after ART ranged between 0% and 14.3%, mostly consisting of symptomatic radiation necrosis regressing after steroids or bevacizumab. Of note, Deng et al 29 report a higher incidence of G ≥ 3 LT following bimodal radiotherapy with a carbon ion boost of 18Gy RBE in 3Gy/ fraction after conventional photon radiotherapy of 50 Gy in 2 Gy/ fraction.…”
Section: Resultsmentioning
confidence: 99%
“…This is of clinical relevance, as a recent analysis of the clinical course of WHO grade 2 meningioma suggested that these low-risk groups indeed have an excellent clinical outcome (as opposed to high-risk, and to a lesser extent also medium-risk). 27 This makes the reliable distinction between these molecular risk profiles very important for a personalized clinical decision-making. However, further studies, including clinical follow-up are needed to investigate clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Our results align well with the clinical observations from Deng et al, who noted a significantly better outcome for low-risk WHO grade 2 meningiomas, while medium- and high-risk tumors shared a similar clinical course. 27 …”
Section: Discussionmentioning
confidence: 99%